Robotic-Assisted Solutions for Invasive Cardiology, Cardiac Surgery and Routine On-Ward Tasks: A Narrative Review - Koulaouzidis, George; Charisopoulou, Dafni; Bomba, Piotr; Stachura, Jaroslaw; Gasior, Pawel; Harpula, Jan; Zarifis, John; Marlicz, Wojciech; Hudziak, Damian; Jadczyk, Tomasz (Journal of cardiovascular development and disease, 2023)
Robots are defined as programmable machines that can perform specified tasks. Medical robots are emerging solutions in the field of cardiology leveraging recent technological innovations of control systems, sensors, actuators, and imaging modalities. Robotic platforms are successfully applied for percutaneous coronary intervention, invasive cardiac electrophysiology procedures as well as surgical operations including minimally invasive aortic and mitral valve repair, coronary artery bypass procedures, and structural heart diseases. Furthermore, machines are used as staff-assisting tools to support nurses with repetitive clinical duties i.e., food delivery. High precision and resolution allow for excellent maneuverability, enabling the performance of medical procedures in challenging anatomies that are difficult or impossible using conventional approaches. Moreover, robot-assisted techniques protect operators from occupational hazards, reducing exposure to ionizing radiation, and limiting risk of orthopedic injuries. Novel automatic systems provide advantages for patients, ensuring device stability with optimized utilization of fluoroscopy. The acceptance of robotic technology among healthcare providers as well as patients paves the way for widespread clinical application in the field of cardiovascular medicine. However, incorporation of robotic systems is associated with some disadvantages including high costs of installation and expensive disposable instrumentations, the need for large operating room space, and the necessity of dedicated training for operators due to the challenging learning curve of robotic-assisted interventional systems.